Preparation method of laser-strengthened wear-resistant hard film
By performing laser scanning and strengthening on the surface of the ceramic hard film, the laser reinforcement layer is formed, which solves the problem of the ceramic hard film being prone to failure on the surface of the metal matrix, and significantly improves its wear resistance and stability.
Patent Information
- Application Number
- CN202411845428.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
Due to the difference in hardness and low toughness of ceramic hard films on the surface of metal substrates, they are prone to cracks, damage, and peeling failure, which limits their application scope.
The laser enhancement technology is combined with the ceramic hard film technology, and laser scanning and strengthening is performed on the surface of the ceramic hard film to form a laser enhancement layer to enhance the hardness support between the substrate and the ceramic hard film.
It effectively avoids the problem of ceramic hard film failure due to the low load-bearing capacity of the matrix and its own low toughness under heavy load, improves the wear resistance of the ceramic hard film, and ensures a stable connection between the ceramic hard film and the matrix.
Smart Images

Figure CN119663229A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface treatment, and in particular to a method for preparing a laser-enhanced wear-resistant hard film. Background Art
[0002] Hard film technology is a surface treatment technology that forms a film layer with a certain hardness on the surface of the workpiece through physical or chemical vapor deposition, thereby improving the mechanical properties of the surface of the workpiece and increasing the service life of the workpiece; in recent years, with the new requirements of material surface mechanics, friction loss, high temperature oxidation resistance and corrosion resistance, hard film technology has developed rapidly and is widely used in machinery, electronics, metallurgy, automobiles, aerospace and other fields. Ceramic hard film has high hardness, low friction coefficient and excellent anti-oxidation performance, and is often used on the surface of cutting tools, abrasive tools and other parts to improve their hardness and wear resistance. However, due to the huge hardness difference between ceramic hard film and metal parts, the soft metal substrate tends to deform under heavy load friction, and thus cannot effectively support the hard film. At the same time, the ceramic hard film has low toughness and high brittleness. Without the support function, the ceramic hard film is prone to cracks, breakage, peeling and failure. This phenomenon is called the "eggshell effect". It can be seen that if the ceramic hard film is directly applied to the surface of the metal substrate, due to the low load-bearing capacity of the metal substrate and the low toughness of the ceramic hard film, the wear resistance of the hard film cannot be fully and effectively exerted, which greatly limits the application scope of the ceramic hard film. Summary of the invention
[0003] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a laser-enhanced wear-resistant hard film. This method effectively solves the low bearing capacity of the metal substrate through the combination of laser strengthening technology and ceramic hard film technology, thereby avoiding problems such as cracks, breakage, and peeling failure in the ceramic hard film, and fully exerts the excellent properties of the ceramic hard film such as high hardness, high wear resistance, high temperature resistance, and corrosion resistance.
[0004] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a laser-enhanced wear-resistant hard film, comprising: Step 1: Pretreatment of the substrate: First, the substrate is degreased and rusted, and then polished; Step 2: preparing a ceramic hard film: preparing a ceramic hard film on the surface of the pre-treated substrate by chemical vapor deposition; Step 3: Laser scanning strengthening: Use laser melting equipment to perform laser scanning strengthening on the surface of the ceramic hard film, so as to form a laser strengthening layer between the substrate and the ceramic hard film.
[0005] Based on further optimization of the above solution, the matrix is made of any alloy of 40Cr, 40CrNiMo, 5CrNiMo and 45 steel.
[0006] Based on the further optimization of the above scheme, the degreasing and rust removal treatment is specifically as follows: the rust and burrs of the substrate are first removed by mechanical grinding, and then the surface of the substrate is degreased and decontaminated with ethyl acetate, and finally the surface of the substrate is dried in a dryer at a drying temperature of 40°C to 50°C.
[0007] Based on further optimization of the above solution, the surface roughness of the substrate after polishing is no greater than 0.6 μm (ie, Ra≤0.6 μm).
[0008] Based on further optimization of the above solution, the thickness of the ceramic hard film is 5 μm to 10 μm.
[0009] Based on further optimization of the above scheme, the ceramic hard film is a TiCN ceramic hard film, and the specific preparation steps are: first, the pre-treated substrate is placed in a reaction chamber, and an inert gas is introduced into the reaction chamber to fill the entire reaction chamber; then, under the conditions of a reaction chamber temperature of 700°C to 850°C and a pressure of 5mbar to 30mbar, TiCl4, CH3CN, N2 and H2 are introduced, wherein: the flow rate of TiCl4 is 4sccm to 5sccm, the flow rate of CH3CN is 0.5sccm to 1sccm, the flow rate of N2 is 10sccm to 15sccm, the flow rate of H2 is 35sccm to 45sccm, and the deposition time is 3h to 4h.
[0010] Based on further optimization of the above solution, the depth of the laser strengthening layer is 50 μm to 150 μm.
[0011] Based on further optimization of the above scheme, the parameters in the laser strengthening process are specifically as follows: power 200W~600W, spot diameter 2mm, defocus amount 2cm, offset 40%~60%, and scanning speed 2mm / s~10mm / s.
[0012] The following are the technical effects of the solution of the present invention: The present application adopts a preparation method of chemical vapor deposition of a specific ceramic hard film in combination with specific laser strengthening. The specific ceramic hard film is first prepared, and then a specific laser melting strengthening process is performed. Under the premise that the laser strengthening does not affect the surface of the ceramic hard film, the laser energy is transmitted to the surface of the alloy substrate through the ceramic hard film to achieve laser strengthening of the surface of the alloy substrate, thereby forming a laser strengthening layer between the alloy substrate and the ceramic hard film. Firstly, the high-hardness strengthening layer after strengthening forms an effective hardness support for the ceramic hard film, avoiding the problems of cracking, breakage, peeling and failure of the ceramic hard film under heavy load due to the low load-bearing capacity of the substrate and its own low toughness (i.e., the ceramic hard film), thereby improving the wear resistance of the ceramic hard film under heavy load. The first is to effectively avoid the high temperature (i.e. 700-850°C) used in the deposition process of the ceramic hard film, which may cause tempering of the laser strengthened layer, resulting in a decrease in the hardness of the laser strengthened layer and an inability to form effective hardness support for the ceramic hard film under heavy loads; the second is to effectively avoid the high temperature (i.e. 700-850°C) used in the deposition process of the ceramic hard film, which may cause tempering of the laser strengthened layer, resulting in a decrease in the hardness of the laser strengthened layer and an inability to form effective hardness support for the ceramic hard film under heavy loads; the third is to block oxygen through the ceramic hard film during the laser strengthening process, thereby avoiding oxidation of the alloy substrate to form an oxide layer during the laser strengthening process, thereby reducing the bonding strength between the alloy substrate and the ceramic hard film (i.e. the oxide layer forms a barrier layer between the alloy substrate and the ceramic hard film), ensuring a stable connection between the ceramic hard film and the laser strengthened layer and the alloy substrate, improving the integrity of the surface treated composite layer, avoiding damage and falling off of the ceramic hard film, and further improving the wear resistance of the ceramic hard film. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Schematic diagram of the structure of the substrate surface treatment composite layer in an embodiment of the present invention.
[0014] Among them, 10, alloy substrate; 20, laser strengthening layer; 30, ceramic hard film. DETAILED DESCRIPTION
[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] Embodiment 1: A method for preparing a laser-enhanced wear-resistant hard film, comprising: Step 1, substrate pretreatment: the substrate is made of 40Cr steel; the substrate is degreased and derusted, specifically: the substrate is first mechanically polished (such as polished with sandpaper, etc.) to remove rust and burrs, and then ethyl acetate is used to degrease and decontaminate the surface of the substrate, and finally the surface of the substrate is dried in a dryer at a drying temperature of 40°C.
[0017] The substrate is then polished (using common polishing methods in the art, which are not specifically limited in this embodiment), and the surface roughness of the substrate after polishing is no greater than 0.6 μm (ie, Ra≤0.6 μm).
[0018] Step 2, preparing a ceramic hard film: using chemical vapor deposition to prepare a ceramic hard film on the surface of the pre-treated substrate, the ceramic hard film uses a high melting point ceramic film with a melting point greater than 3000° C.; The thickness of the ceramic hard film is 5 μm, and the ceramic hard film is a TiCN ceramic hard film. The specific preparation steps are: first, place the substrate pretreated in step one in a reaction chamber, and introduce an inert gas into the reaction chamber (the inert gas is any one of helium and argon) to fill the entire reaction chamber with the inert gas; then, under the conditions of a reaction chamber temperature of 700°C and a pressure of 6 mbar, introduce TiCl4, CH3CN, N2 and H2, wherein: the flow rate of TiCl4 is 4 sccm, the flow rate of CH3CN is 0.5 sccm, the flow rate of N2 is 10 sccm, the flow rate of H2 is 35 sccm, and the deposition time is 3 hours.
[0019] Step 3: Laser scanning strengthening: Use laser melting equipment to perform laser scanning strengthening on the surface of the ceramic hard film, so as to form a laser strengthening layer between the substrate and the ceramic hard film; wherein, the depth of the laser strengthening layer is 50μm, and the parameters in the laser strengthening process are as follows: power 200WW, spot diameter 2mm, defocus amount 2cm, offset 40%, and scanning speed 10mm / s.
[0020] Embodiment 2: A method for preparing a laser-enhanced wear-resistant hard film, comprising: Step 1, substrate pretreatment: the substrate is made of 40CrNiMo steel; the substrate is degreased and derusted, specifically: the substrate is first mechanically polished (such as polished with sandpaper, etc.) to remove rust and burrs, and then ethyl acetate is used to degrease and decontaminate the surface of the substrate, and finally the surface of the substrate is dried in a dryer at a drying temperature of 45°C.
[0021] The substrate is then polished (using common polishing methods in the art, which are not specifically limited in this embodiment), and the surface roughness of the substrate after polishing is no greater than 0.6 μm (ie, Ra≤0.6 μm).
[0022] Step 2, preparing a ceramic hard film: using chemical vapor deposition to prepare a ceramic hard film on the surface of the pre-treated substrate, the ceramic hard film uses a high melting point ceramic film with a melting point greater than 3000° C.; The thickness of the ceramic hard film is 7.5 μm, and the ceramic hard film is a TiCN ceramic hard film. The specific preparation steps are: first, place the substrate pretreated in step one in a reaction chamber, and introduce an inert gas into the reaction chamber (the inert gas is any one of helium and argon) to fill the entire reaction chamber with the inert gas; then, under the conditions of a reaction chamber temperature of 775°C and a pressure of 8 mbar, introduce TiCl4, CH3CN, N2 and H2, wherein: the flow rate of TiCl4 is 4.5 sccm, the flow rate of CH3CN is 0.75 sccm, the flow rate of N2 is 12.5 sccm, the flow rate of H2 is 40 sccm, and the deposition time is 3.5 h.
[0023] Step 3: Laser scanning strengthening: Use laser melting equipment to perform laser scanning strengthening on the surface of the ceramic hard film, so as to form a laser strengthening layer between the substrate and the ceramic hard film; wherein, the depth of the laser strengthening layer is 100μm, and the parameters in the laser strengthening process are as follows: power 400W, spot diameter 2mm, defocus amount 2cm, offset 50%, and scanning speed 6mm / s.
[0024] Embodiment 3: A method for preparing a laser-enhanced wear-resistant hard film, comprising: Step 1, substrate pretreatment: the substrate is made of 5CrNiMo steel; the substrate is degreased and derusted, specifically: the substrate is first mechanically polished (such as polished with sandpaper, etc.) to remove rust and burrs, and then ethyl acetate is used to degrease and decontaminate the surface of the substrate, and finally the surface of the substrate is dried in a dryer at a drying temperature of 50°C.
[0025] The substrate is then polished (using common polishing methods in the art, which are not specifically limited in this embodiment), and the surface roughness of the substrate after polishing is no greater than 0.6 μm (ie, Ra≤0.6 μm).
[0026] Step 2, preparing a ceramic hard film: using chemical vapor deposition to prepare a ceramic hard film on the surface of the pre-treated substrate, the ceramic hard film uses a high melting point ceramic film with a melting point greater than 3000° C.; The thickness of the ceramic hard film is 10 μm, and the ceramic hard film is a TiCN ceramic hard film. The specific preparation steps are: first, place the substrate pretreated in step one in a reaction chamber, and introduce an inert gas into the reaction chamber (the inert gas is any one of helium and argon) to fill the entire reaction chamber with the inert gas; then, under the conditions of a reaction chamber temperature of 850°C and a pressure of 10 mbar, introduce TiCl4, CH3CN, N2 and H2, wherein: the flow rate of TiCl4 is 5 sccm, the flow rate of CH3CN is 1 sccm, the flow rate of N2 is 15 sccm, the flow rate of H2 is 45 sccm, and the deposition time is 4 hours.
[0027] Step 3: Laser scanning strengthening: Use laser melting equipment to perform laser scanning strengthening on the surface of the ceramic hard film, so as to form a laser strengthening layer between the substrate and the ceramic hard film; wherein, the depth of the laser strengthening layer is 150μm, and the parameters in the laser strengthening process are as follows: power 600W, spot diameter 2mm, defocus amount 2cm, offset 60%, and scanning speed 2mm / s.
[0028] Embodiment 4: A highly wear-resistant ceramic hard film on the surface of an alloy substrate is prepared by any method as in Examples 1 to 3, comprising an alloy substrate 10, a laser strengthening layer 20 and a ceramic hard film 30, wherein the alloy substrate 10 is made of any one of 40Cr, 40CrNiMo, 5CrNiMo and 45 steel; the laser strengthening layer 20 is located between the alloy substrate 10 and the ceramic hard film 30, and its depth is 50μm to 150μm; the ceramic hard film 30 is a TiCN ceramic hard film, and its thickness is 5μm to 10μm.
[0029] Comparative Example 1: A method for preparing a hard film, comprising: Step 1: substrate pretreatment: the substrate pretreatment step is consistent with step 1 in Example 2, and the substrate is made of 40CrNiMo steel.
[0030] Step 2, laser scanning strengthening: laser melting equipment is used to perform laser scanning strengthening on the surface of the substrate after pretreatment, so as to form a laser strengthening layer on the surface of the substrate; wherein, the depth of the laser strengthening layer is 100μm, and the parameters in the laser strengthening process are specifically: power 400W, spot diameter 2mm, defocus amount 2cm, offset 50%, and scanning speed 6mm / s.
[0031] Step 3, preparation of ceramic hard film: use chemical vapor deposition to prepare a ceramic hard film on the surface of the substrate after laser scanning and strengthening; the thickness of the ceramic hard film is 7.5μm, and the ceramic hard film is a TiCN ceramic hard film. The specific preparation steps are: first, place the substrate after laser scanning and strengthening in step 2 in a reaction chamber, and introduce an inert gas into the reaction chamber (the inert gas is any one of helium and argon) to fill the entire reaction chamber with the inert gas; then, under the conditions of a reaction chamber temperature of 775°C and a pressure of 8mbar, introduce TiCl4, CH3CN, N2 and H2, wherein: the flow rate of TiCl4 is 4.5sccm, the flow rate of CH3CN is 0.75sccm, the flow rate of N2 is 12.5sccm, the flow rate of H2 is 40sccm, and the deposition time is 3.5h.
[0032] Comparative Example 2: A method for preparing a hard film, comprising: Step 1: substrate pretreatment: the substrate pretreatment step is consistent with step 1 in Example 2, and the substrate is made of 40CrNiMo steel.
[0033] Step 2, preparation of ceramic hard film: use chemical vapor deposition to prepare a ceramic hard film on the surface of the pre-treated substrate. The thickness of the ceramic hard film is 7.5μm. The ceramic hard film is a Si3N4 ceramic hard film. The specific preparation steps are as follows: first, place the substrate pre-treated in step 1 in a reaction chamber, and introduce an inert gas into the reaction chamber (the inert gas is any one of helium and argon) to fill the entire reaction chamber with the inert gas; then, under the conditions of a reaction chamber temperature of 800°C and a pressure of 0.2mbar, introduce SiH4, NH3 and H2, and control the gas flow rate and deposition time to obtain a Si3N4 ceramic hard film of a specific thickness (for example: the flow rate of SiH4 is 10sccm, the flow rate of NH3 is 5sccm, the flow rate of H2 is 25sccm, and the deposition time is 10min).
[0034] Step 3: Laser scanning strengthening: the same as the laser scanning strengthening step of step 3 in Example 2.
[0035] Comparative Example 3: A method for preparing a hard film, comprising: Step 1: substrate pretreatment: the substrate pretreatment step is consistent with step 1 in Example 2, and the substrate is made of 40CrNiMo steel.
[0036] Step 2, preparation of ceramic hard film: use chemical vapor deposition to prepare a ceramic hard film on the surface of the pre-treated substrate. The thickness of the ceramic hard film is 7.5μm. The ceramic hard film is an Al2O3 ceramic hard film. The specific preparation steps are as follows: first, place the substrate pre-treated in step 1 in a reaction chamber, and introduce an inert gas into the reaction chamber (the inert gas is either helium or argon) to fill the entire reaction chamber with the inert gas; then, under the conditions of a reaction chamber temperature of 1000°C and a pressure of 2mbar, introduce Al (CH3)3 and O2, and control the gas flow rate and deposition time to obtain an alumina ceramic hard film of a specific thickness.
[0037] Step 3: Laser scanning strengthening: the same as the laser scanning strengthening step of step 3 in Example 2.
[0038] Comparative Example 4: A method for preparing a hard film, comprising: Step 1: substrate pretreatment: the substrate pretreatment step is consistent with step 1 in Example 2, and the substrate is made of 40CrNiMo steel.
[0039] Step 2, preparation of ceramic hard film: use chemical vapor deposition to prepare a ceramic hard film on the surface of the pre-treated substrate. The thickness of the ceramic hard film is 7.5μm. The ceramic hard film is a TiAlN ceramic hard film. The specific preparation steps are: first, place the substrate pre-treated in step 1 in a reaction chamber, and introduce an inert gas into the reaction chamber (the inert gas is either helium or argon) to fill the entire reaction chamber with the inert gas; then, under the conditions of a reaction chamber temperature of 1000°C and a pressure of 2mbar, introduce TiCl4, AlCl3 and NH3, and control the gas flow rate and deposition time to obtain a TiAlN ceramic hard film of a specific thickness.
[0040] Step 3: Laser scanning strengthening: the same as the laser scanning strengthening step of step 3 in Example 2.
[0041] The wear rates of the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were measured using a reciprocating friction and wear tester (HSR-2M, China) under a load of 20 N, a sliding length of 5 mm, a sliding frequency of 5 Hz, and a duration of 1800 s (the environmental conditions of the tests were the same). The measurement results are shown in the following table:
[0042] It can be seen from the above table that: in the present application, a laser-strengthened layer is formed between the substrate and the ceramic hard film layer by first preparing a TiCN hard ceramic film layer and then performing laser scanning strengthening. Compared with first forming a laser-strengthened layer on the substrate surface and then preparing TiCN, the wear rate is significantly reduced (i.e., comparison between Example 2 and Comparative Example 1), which can effectively prove that the laser-strengthened layer prepared by the scheme of the present application forms an effective support for the hard ceramic film layer and the laser-strengthened layer is not damaged, thereby significantly improving the wear resistance of the ceramic hard film layer. At the same time, in Comparative Examples 2, 3, and 4, the Si3N4 ceramic hard film, Al2O3 ceramic hard film, and TiAlN ceramic hard film were prepared and then laser strengthened. Compared with the samples prepared by Si3N4 ceramic hard film, Al2O3 ceramic hard film, and TiAlN ceramic hard film alone (i.e., without laser strengthening, only the ceramic hard film layer was prepared on the substrate surface), the wear rate of the samples was (the wear rate of the samples prepared by Si3N4 ceramic hard film alone under the same conditions was 4.33x10 -7 mm 3 / N·m, the wear rate of the sample prepared with Al2O3 ceramic hard film alone under the same conditions is 4.62x10 -7 mm 3 / N·m, the wear rate of the sample prepared with TiAlN ceramic hard film alone under the same conditions is 4.45x10 -7 mm 3 / N·m) does not decrease significantly, which proves that in the method of first preparing the ceramic hard film layer and then laser strengthening in Comparative Examples 2 to Comparative Examples 4, the laser strengthening does not form a stable and effective support for the ceramic hard film layer as in the present application.
Claims
1. A method for preparing a laser-enhanced wear-resistant hard film, characterized in that: include: Step 1: Pretreatment of the substrate: First, the substrate is degreased and rusted, and then polished; Step 2: preparing a ceramic hard film: preparing a ceramic hard film on the surface of the pre-treated substrate by chemical vapor deposition; Step 3: Laser scanning strengthening: Use laser melting equipment to perform laser scanning strengthening on the surface of the ceramic hard film, so as to form a laser strengthening layer between the substrate and the ceramic hard film.
2. The method for preparing a laser-enhanced wear-resistant hard film according to claim 1, characterized in that: The matrix is made of any alloy of 40Cr, 40CrNiMo, 5CrNiMo and 45 steel.
3. A method for preparing a laser-enhanced wear-resistant hard film according to claim 1 or 2, characterized in that: The degreasing and rust removal treatment is specifically as follows: the rust and burrs of the substrate are first removed by mechanical grinding, and then the surface of the substrate is degreased and decontaminated with ethyl acetate, and finally the surface of the substrate is dried in a dryer at a drying temperature of 40°C to 50°C.
4. A method for preparing a laser-enhanced wear-resistant hard film according to claim 1 or 2, characterized in that: The surface roughness of the substrate after polishing is no greater than 0.6 μm.
5. The method for preparing a laser-enhanced wear-resistant hard film according to claim 3, characterized in that: The ceramic hard film is a TiCN ceramic hard film, and the specific preparation steps are: first, the pre-treated substrate is placed in a reaction chamber, and an inert gas is introduced into the reaction chamber to fill the entire reaction chamber; then, TiCl4, CH3CN, N2 and H2 are introduced under the conditions of a reaction chamber temperature of 700°C to 850°C and a pressure of 5mbar to 30mbar. Among them: the flow rate of TiCl4 is 4sccm~5sccm, the flow rate of CH3CN is 0.5sccm~1sccm, the flow rate of N2 is 10sccm~15sccm, the flow rate of H2 is 35sccm~45sccm, and the deposition time is 3h~4h.
6. The method for preparing a laser-enhanced wear-resistant hard film according to claim 5, characterized in that: The parameters in the laser strengthening process are specifically: power 200W-600W, spot diameter 2mm, defocusing amount 2cm, offset 40%-60%, and scanning speed 2mm / s-10mm / s.